Unions and Strikes with Asymmetric Information - Hayes, Beth (Journal of Labor Economics, 1984)
Strikes seem to be a Pareto-inefficient outcome of bargaining between a union and a firm; however, this paper shows that strikes can be the outcome of rational behavior by both agents. If the firm has more information than the union concerning the state of nature, the union can use strikes as a way of gaining information. The paper uses an asymmetric information model where the firm has information about the state (i.e., profitability) that the union does not know. The schedule of wage offers by the union then depends on the probability that a given state will occur.